Biodiesel synthesis from PFAD using heterogeneous sulfonated-glucose catalysts - Mavakumba, Kefas Haruna (2018)
The use of heterogeneous catalysts for biodiesel production is known to mitigate technical issues associated with the use of homogeneous catalysts which are contributed mainly by costly separations and purification steps. However, the limitation in catalytic active sites and stability are issues that deter the effectiveness of the heterogeneous system. In principle, the sugar carbon based catalysts can address these problems. In this study, sulfonated carbonized glucose catalyst was synthesized and utilized for biodiesel synthesis through a single step esterification of non-edible palm fatty acid distillate (PFAD) in an oscillatory flow reactor (OFR). The optimum sulfonation conditions obtained from the use of RSM-CCRD in the catalyst synthesis were 11.25 % of (NH4)2SO4 concentration, 5.34 hr of time, 25.16 ml of concentrated H2SO4 and 151.15 oC of temperature which achieved 93.30 % free fatty acid (FFA) conversion and 91.87 % FAME yield. The optimized sulfonated catalyst underwent detailed characterization utilizing FTIR, XRD, TGA, TPD-NH3, FESEM, EDX and BET. Results showed it had a stable amorphous polycyclic aromatic structure with BET surface area of 4.47 m2/g and 5.92 mmol/g acid sites density thereby exhibiting high catalytic activity in the esterification reaction. The optimization of process conditions in the batch reactor achieved 93.23 % FFA conversion at optimized conditions of 4 wt.% of sulfonated catalyst, 65 oC reaction temperature, 10:1 methanol to PFAD molar ratio and 4 h of reaction time. The catalyst was active up to five cycles re-uses without reactivation. The kinetics study of the esterification of PFAD and methanol using the sulfonated glucose acid catalyst performed in the batch reflux reactor proved that it was an irreversible reaction due to the use of excess methanol. The experimental data was best interpreted with bimolecular (equimolar) second order model. The rate constant of the reaction (k) from the kinetics study determined at various temperatures ranged from 0.0002 to 0.00053 and the activation energy was calculated to be 55.08 kJmol- 1. The developed kinetics model and the experimental data are in good agreement. The biodiesel production with optimized solid acid catalyst in OFR was successfully performed. The OFR achieved maximum of 97.1 % FFA conversion to FAME and >94 % yield. The optimum operating conditions at optimum conversion were 2.5 wt.% of sulfonated catalyst, 60 oC temperature, 9:1 methanol to PFAD molar ratio, 6 Hz oscillation frequency, and 50 min reaction time. The sulfonated catalyst showed reasonable catalytic activity for up to four cycle’s reuse in the OFR achieving about 80 % conversion at the fourth cycle. The performance of OFR was better than the reflux batch reactor in terms of conversion and operating conditions due to the efficient fluid mixing mechanism which resulted in reaction time reduction as well as enhancing heat and mass transfer. In addition, the properties of the PFAD FAME produced from the OFR showed a pour point and cloud point of 12 oC and 15 oC, respectively. The low temperature characteristics of the biodiesel were slightly above the ASTM standard due to high FFA constituent of the PFAD. Most of the other properties are within standard specifications for ASTM D6751 and EN 14214. The biodiesel produced is not suitable for winter grade biodiesel due to its high pour point. In conclusion, the synthesized modified sulfonated glucose catalyst has proven to be a catalytically active and stable heterogeneous acid catalyst for biodiesel synthesis from high FFA PFAD feedstock especially in the OFR system.